Orthodontic Treatment to Improve Hip Joint Mobility and Balance - Fujii, Yoshiro (The Journal of Dentists, 2015)
The case subject is a 10-year-old girl with a history of strong left hip joint flexibility issues and milder right hip joint flexibility issues. The main cause of this disorder was confirmed to be the misalignment of her lower front teeth. As soon as dental orthodontic devices were attached on her lower teeth, the movement of her left hip joint improved. The mobility of both hip joints further improved as the orthodontic treatment progressed. Furthermore, she was able to maintain her balance for longer periods of time. However, the underlying mechanism, which leads to such a quick and extensive improvement, is unclear. Further studies are required.